Study of the Antiviral Activity of Adamantane-Containing Chemical Compounds - I. I. LYUBIMOV; E. I. ISAEVA; E. N. VETROVA; A. V. LAVROVA; N. M. GRETSKAYA; I. V. SERKOV; V. V. BEZUGLOV; G. A. GALEGOV (Антибиотики и Химиотерапия, 2022)
Influenza and coronavirus infections are especially dangerous due to being capable of causing pandemics and clinical complications in the nervous and cardiovascular systems, as well as exacerbation of chronic diseases (diabetes mellitus, heart failure, chronic obstructive bronchopneumonia, etc.), which can cause delayed death, especially in children under two years of age, the elderly, and individuals with poor health. The aim of the study was to search for compounds effective against these two topical viruses which possess constant epidemic activity — influenza virus and betacoronavirus — among new adamantane derivatives containing a NO-donor fragment or a dopamine residue. Another purpose of the study was determination of cytotoxicity and antiviral activity of compounds on cell lines permissive for influenza virus and betacoronavirus. The antiviral activity of 6 adamantane derivatives against strains of the influenza virus (H1N1) and betacoronavirus was studied. It was established that the NO-donor derivative of aminoadamantane succinate and the dopamine derivative of adamantanebenzoic acid had the greatest ability to suppress the development of the influenza virus with a chemotherapeutic index above 60. No promising compounds against betacoronavirus were identified.